Perencanaan Rekrutmen Tenaga Pendidik di Yayasan MIS Bidayatul Hidayah Rafa Kabupaten Deli Serdang - Siti Aisyah; Abdullah Fikri; Sholehuddin SN (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The aim of this research is to understand the recruitment planning of educators at MIS Bidayatul Hidayah Rafa Foundation in Deli Serdang Regency. This research employs a qualitative approach with a descriptive research type. Data collection techniques were carried out through interviews, observations, and documentation studies. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The research subjects are the head of the madrasa, teachers, and students at MIS Bidayatul Hidayah Rafa. The results of the study indicate that the recruitment planning of educators at the MIS Bidayatul Hidayah Rafa Foundation has been carried out well, including needs analysis, qualification determination, and the selection process. In conclusion, the recruitment planning of educators at the MIS Bidayatul Hidayah Rafa Foundation has been conducted in accordance with existing procedures.